2018
DOI: 10.1111/jan.13690
|View full text |Cite
|
Sign up to set email alerts
|

The physical environment and patients’ activities and care: A comparative case study at three newly built stroke units

Abstract: Patients' activity levels and interactions appeared to vary with the design of the physical environments of stroke units. Stroke guidelines focused on health status assessments, avoidance of bed-rest and early rehabilitation require a supportive physical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…The fact that patients in the current study were observed in their room 73% of their day certainly reveals flaws in the environment, especially as they were observed to be in bed for more than 60% of the time spent in their room. A study comparing different stroke units found that patients treated at a unit with shared bedrooms were more active than patients at a unit with exclusively single bedrooms (25). Another study found that stroke units serving food in communal areas had more physically active patients compared with units in which food was served in patients' rooms (26).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that patients in the current study were observed in their room 73% of their day certainly reveals flaws in the environment, especially as they were observed to be in bed for more than 60% of the time spent in their room. A study comparing different stroke units found that patients treated at a unit with shared bedrooms were more active than patients at a unit with exclusively single bedrooms (25). Another study found that stroke units serving food in communal areas had more physically active patients compared with units in which food was served in patients' rooms (26).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed an association between the well-being of patients and staff at healthcare facilities and the design of the physical environment [12][13][14][15]. In stroke units, the physical environment has been described as essential for patient activities and care [16][17][18]. Changes in the physical environment have been found to influence patient activity and social interactions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the physical environment have been found to influence patient activity and social interactions [16]. In a recent study, patients were found to have higher levels of activity in a stroke unit that had a combination of single and multibed room designs compared to a stroke unit with only a singleroom design [18]. However, the interplay between the physical environment of stroke units and multi-professional teamwork has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-documented that one of the factors influencing patient rehabilitation is the physical environment of recovering stroke patients. [45] As a result, various components of the NICU and SW ranging from the composition of care teams to the architectural features of the building have been considered for their potential to facilitate or hamper recovery from stroke. [67]…”
Section: Introductionmentioning
confidence: 99%